Churches, Returns Directive, and the immigration issues in the European Union - S A Mudrov (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2016)
This article analyses the role of Christian churches in the European Union immigration policy with the special focus on the elaboration and adoption of the Directive on common standards and procedures in Member States for returning illegally staying third-country nationals (the so-called ‘Returns Directive’). The author briefly discusses the main developments of the European Union policy in the area of migration and asylum, and then identifies the key Christian organizations, which work in this sphere at the European Union level. This part of the article is followed by the detailed analysis of the process of adoption of the Returns Directive. It was the first legislative proposal made under the co-decision mechanism in the area of migration and asylum. Christian organizations were involved in this process almost from its beginning exercising their influence via statements and negotiations. Although many Churches’ suggestions were not taken into account, this happened under the great diversity of opinions of the stakeholders, which made the promotion of Churches’ perspective very complicated. Overall, the author considers necessary to admit that Christian organizations with all their experience and expertise proved to be respected partners of the European Union policy-making in the sphere of migration and asylum.